Anodic Stripping Voltammetry at Nanoelectrodes: Trapping of Mn2+ by Crown Ethers. (20th April 2015) - Danis, Laurence; Gateman, Samantha Michelle; Snowden, Michael Edward; Halalay, Ion C.; Howe, Jane Y.; Mauzeroll, Janine
Abstract: The work presented here describes the development and characterization of platinum-mercury hemispherical nanoelectrodes for the spatially resolved quantitative detection of manganese cations. The electrochemical probes were made by electrodeposition of metallic mercury from a mercuric ion solution onto Pt/quartz laser-pulled concentric disk nanoelectrodes (with disk radii ranging from 3 to 500 nm). The nanoelectrodes were characterized by steady-state voltammetry, scanning electrochemical microscopy, environmental scanning electron microscopy, energy-dispersive X-ray spectroscopy and calibrated with respect to the concentration of Mn 2+ ions using anodic stripping voltammetry. The fully characterized probes were employed for the quantitative detection of Mn 2+ . The technique has been used to evaluate the impact of a novel approach for mitigating the undesirable consequences of manganese dissolution in Li-ion batteries.